EMPLOYEE PERCEPTIONS OF JOB SATISFACTION: COMPARATIVE STUDY ON INDIAN BANKS - Arunima Shrivastava,; Pooja Purang, (Asian Academy of Management Journal, 2009)
The present study examined the job satisfaction level of a public sector and private sector bank employees in India. The sample consisted of 340 bank employees from both sectors. Job Diagnostic Survey by Hackman and Oldham (1975) was used to ascertain the level of job satisfaction. This study used independent samples t-test and qualitative analysis to study the differences in employee attitudes. Results indicated that the means of the public and private banks were significantly different from each other. It was found that private sector bank employees perceive greater satisfaction with pay, social, and growth aspects of job as compared to public sector bank employees. On the other hand, public sector bank employees have expressed greater satisfaction with job security as compared to private sector bank employees. The findings of the study highlight important satisfiers and dissatisfiers present in the job and suggest both the banks to take performance initiatives in the areas where employees have reported reduced satisfaction.